Strategies for Private-Sector Development and Civil-Service Reform in the Kurdistan Region—Iraq - Michael L. Hansen, Howard J. Shatz, Louay Constant, Alexandria C. Smith, Krishna B. Kumar, Heather Krull, Artur Usanov (RAND Corporation, 2014)
This monograph presents strategies to increase private-sector employment and to reemploy civil-service workers in the private sector in the Kurdistan Region—Iraq (KRI). Prepared for and at the request of the Kurdistan Regional Government (KRG) under the auspices of Dr. Ali Sindi, Minister of Planning, this monograph is based on a variety of methods and analyses. These include a review of the existing literature, analyses of survey data, analysis of Kurdistan regional and Iraqi national documents and laws, and a qualitative assessment of numerous conversations with government officials and private-sector employers. The findings should be of interest to those concerned with private-sector development and civil-service reform more generally and to those with a regional focus on the Middle East and North Africa. This research was undertaken within RAND Labor and Population. RAND Labor and Population has built an international reputation for conducting objective, high-quality, empirical research to support and improve policies and organizations around the world. Its work focuses on children and families, demographic behavior, education and training, labor markets, social welfare policy, immigration, international development, financial decisionmaking, and issues related to aging and retirement with a common aim of understanding how policy and social and economic forces affect individual decisionmaking and human well-being.